Zoneamento climático local: a geografia do clima em Vila Velha (ES, Brasil) como subsídio ao planejamento e ordenamento do território - Nascimento, Fabricio Holanda do (2024)
The evolution of society, due to the development of technology and science, as well as population growth, leads to an increase in urban areas and, consequently, to the problems associated with urbanization, both social and environmental, particularly regarding the climate of a given location. Therefore, it is of fundamental importance that research be developed with the aim of understanding this society-nature relationship. Both urban and rural areas benefit from climate studies from a geographical perspective, as these studies make it possible to perceive climate patterns that help in the development of public policies, with a view to developing more sustainable and resilient cities and rural areas. In this context, this research had the main objective of identifying and mapping the Local Climate Zones (LCZ) in the municipality of Vila Velha, State of Espírito Santo, Brazil. To this end, a mapping of the LCZs was developed, according to the methodology of Stewart; Oke (2012), Demuzere et al. (2021), with the aid of the LCZ Generator, a web application for mapping LCZ. To this end, several maps derived from satellite images (Remote Sensing) were prepared, including Earth's surface temperature (TST) models, Normalized Difference Vegetation Index (NDVI) and Normalized Difference Built-up Area Index (NDBI), considering a historical series from 2018-2022, Landsat-8 satellite images, available on the USGS website. As secondary objectives, we sought to understand the main atmospheric systems that influence the weather and climate conditions of the study area, through the analysis of synoptic charts and meteorological satellite images, available on the websites of the Marinha do Brasil and CPTEC, respectively, as well as the rhythmic analysis of the climate and to prepare scientific material that can support the municipality's decision-makers in municipal urban planning and organization. In order to achieve the objectives adequately, readings were also carried out on the main theories that guided this research, namely: climate theories – both those that define it as a static factor (Köppen) and those that understand it as dynamic (Max Sorre) –, climate geography and the methodology of Local Climate Zones (Stewart; Oke). In addition, field work was carried out using the mobile transect technique to record air temperature and relative humidity data using measuring instruments, the Minipa Thermo-hygrometer, model MT-241, which was attached to a PVC pipe, during hot days, between February and May 2024. This research is important because Vila Velha lacks scientific studies on the subject in question and, therefore, fills a gap in knowledge of the local climate from a geographical perspective. The results were satisfactory and allowed us to draw a series of conclusions. Vila Velha, as it is a typically tropical municipality, has distinct local climate zones, notwithstanding the specificities of the municipality; the remote sensing derivatives (TST, NDVI and NDBI) allowed us to perceive a strong correlation between urbanization and the absence of green spaces with the increase in surface temperature over the period evaluated (2018-2022); the mobile transect contributed significantly to the understanding of the local climate and perception of the correlation between the typologies of land use and cover and the thermal and humidity field in Vila Velha. Thus, it is expected that, through this theoretical and methodological material, managers and society will be able to understand the local climate of Vila Velha and the relationship between urbanization and the elements of the local atmosphere, and perceive them as key elements in defining planning and land use planning that considers the quality of life of the population that lives there and the natural environment.